Effect of metal nanoparticles on microbial community shift and syntrophic metabolism during anaerobic digestion of Azolla microphylla. Issue 5 (October 2021) - Kaur, Manpreet; Sahoo, Prakash.C.; Kumar, Manoj; Sachdeva, Sarita; Puri, S.K.
Abstract: Supplementation of anaerobic digesters with conductive nanoparticles (NPs) is considered as a potential approach for augmenting methanogenesis, however, their impact on microbial diversity, methanogenesis routes and metabolic pathways appear to differ depending on the substrate and operational conditions. Hence, in the present study, using metagenomics and KEGG pathway analysis, an attempt was made to gain an insight into the influence of two NPs viz ., Fe3 O4 and Ni, on the microbial composition and metabolic pathways during anaerobic digestion (AD) of Azolla microphylla . Results showed that addition of both Fe3 O4 and Ni NPs at optimal concentration significantly accelerated the substrate degradation rate (89.8%) thereby enhancing the biomethane yield by 49.1% in anaerobic reactor (M3) supplemented with NPs as compared to control (M0). The dominance of microbial species ( Enterococcus sp.) belonging to Firmicutes phylum in M3 reactor, indicated an efficient hydrolysis of Azolla biomass, owing to abundance of glycoside hydrolase (GH)-coding genes in their genome. Metagenomic analysis showed the enrichment of Geobacter sp . and Methanosaeta harundinacea in NPs-amended reactor confirming syntrophic metabolism of AD intermediate products that could have resulted in enhanced hydrogenotrophic methanogenesis via DIET. Predominance of Fe (III) reducing acetoclastic methanogen Methanosarcina acetivorans in NPs-fed reactor might also have been attributed to enhanced methane production. KEGG pathway analysis also showed an enhancement of major metabolic pathways viz., Carbohydrate metabolism, Methane metabolism and Lipid metabolism, in M3 reactor which further signifies the stimulatory effect of NPs. Graphical Abstract: ga1 Highlights: Nanoparticles (NPs) improved the methane yield by 49.1% as compared to control. Abundance of Enterococcus sp. enhanced cellulose and hemicellulose hydrolysis rate. NPs augmented methanogenesis by promoting electric microbial syntrophy via DIET. Enrichment of Methanosarcina acetivorans favored acetoclastic methanogenesis.